Bairro rural-bairro urbano: um revisão conceitual - Halley, Bruno Maia (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
The text aims to present a conceptual review of the neighborhood term since his initial studies focused on rural areas, passing by later reading within the urban context. In Brazil, the first analyzes, both in Sociology and in Geography, were based on the concept of “neighborhoods hillbillies” in the countryside of the state of São Paulo, that after unfolded in the last century, in analyzes of urban cells in Rio de Janeiro and in Sao Paulo. After these traditional studies, and a hiatus of work about the neighbourhood (1958-1982), has the advent in 1980/90, a new series of studies, they supported, especially in two theoretical strands of geogra- phy: a humanistic-cultural and marxist-lefebvrean. It is therefore through these different perspectives that the text supports its conceptual revisiting about the neighborhood.